PENERAPAN MODEL COOPERATIVE LEARNING TIPE EXAMPLE NON EXAMPLE BERBANTUAN MEDIA ICT UNTUK MENINGKATKAN PRESTASI BELAJAR PESERTA DIDIK KELAS III SDN 171 REJANG LEBONG - Niky Luthfi Pratiwi; Nani Yuliantini; Herman Lusa (Universitas Bengkulu, 2022)
This study aims to describe the Example Non Example Learning model assisted by ICT media and to improve the learning achievement of class III students of SDN 171. This type of research is classroom action research (PTK) with two cycles each cycle consisting of three meetings. The research subjects were teachers and students of class III SDN 171. The research subjects were teachers and students of class III SDN 171. Data collection techniques using observation and test techniques. The research instrument was an observation sheet for the model implementation and a test sheet. The data analysis technique used qualitative and quantitative analysis techniques. The results showed that the implementation of the Example Non Example model increased from cycle I to cycle II. This can be seen from the implementation of the Example Non Example model with steps namely orientation, group work, quizzes, awards and evaluations which can improve student learning achievement. This can be seen in the value of cycle I in Indonesian subjects, the class average value of 64.41 with classical learning completeness 52.94% in cycle II the class average value of 78.72 with classical learning completeness 82.35%. PPKn subjects of the first cycle of the average value of grade 67 with classical learning completeness 64.70% in the second cycle class average value of 78.35 with 88.23% classical learning completeness. It can be concluded that the application of the Example Non Example Cooperative Learning model assisted by ICT